Assessment of Health Professionals' Knowledge of Risk Factors in the Performance of Home Radiography - Panagiotis Bidikoudis; Konstantinos Athanasakis; Christos Michail; Georgios Farantos; Georgios Dounias (European Scientific Journal, ESJ, 2024)
Aim and purpose: The knowledge of health professionals about the potential risks of using ionizing radiation plays an important role in protecting themselves and patients. The use of mobile radiography units poses several threats to workers such as radiation exposure, ergonomic injuries and musculoskeletal disorders from the constant use of lead feet and moving the portable radiography machine. The aim of the study is to highlight the knowledge background of healthcare professionals on radiation and radiation protection. Methodology: 72 questionnaires were distributed and 60 were returned with an overall response rate of 83%. The main sections addressed through the questionnaire were demographic data, knowledge background on radiation dose and radiation protection rules and measures. Statistical analysis of the data was performed using SPSS software. Results: From the results, the deficit of the knowledge background of health professionals on radiation and radiation protection is evident. It emerged that health professionals, especially medical doctors - radiologists have knowledge of the dose received by the patient when performing a chest X-rayin a percentage of 75%, 6.6% stated that they rarely or never use a protective lead apron, 5% of the respondents stated that they never use a personal dosimeter. Conclusion: The guidelines for radiation protection of workers and patients when performing home radiography should be based on the pillars of continuous training of staff, but also on adherence to the very basic principle of justification.